Tracing the shadows: Inside the European illegal arms market – the case of Poland: Rozpraszając mrok. Nielegalny rynek broni w Europie na przykładzie Polski (Archives of Criminology, 2023)
Each year approximately 600–700 homicides are committed with firearms in the EU. Despite this, the subject of the illicit arms market in Europe has only recently become the focus of in-depth criminological study. Moreover, so far, few studies have been conducted to analyse in-depth the impact of illicit firearms trafficking on gun violence in Europe. This situation is hindered by a lack of relevant, detailed quantitative data in many European countries. At the same time, it had been unequivocally stated in the literature that this type of crime is a key area of criminal activity for organised groups and associations. The study of the illicit arms market is difficult, since, first of all, there are few sources of reliable information and data, and secondly, the relevant law enforcement organisations usually refuse to assist on the grounds of protecting classified information. The police and intelligence agencies consider the illicit arms market to be an especially sensitive issue. In this research data was retrieved from state databases, as well as official reports and statements. Public entities released their data under the Act on Access to Public Information. The essential data source was court cases from 2010–2017. This research material was supplemented with press materials concerning trafficking, seizing, manufacturing and converting firearms, which offered a high level of detail and a large number of variables. Depending on the segment, data from periods encompassing from 7 to 19 years were compiled and analysed. The purpose of the study was to demonstrate quantitative and qualitative changes in the supply of firearms and ammunition on the Polish illicit firearms market, driven by various factors, including international influences, primarily the Ukraine factor after 2014. Due to Poland’s unique location and other reasons, these fluctuations may have an impact on the public safety of states participating in the Schengen Agreement in relation to organised crime, extremism and terrorism. A better intelligence picture of the illicit firearms market in Europe is crucial for developing adequate policy responses to combat illegal firearms trafficking and for enhancing operational cooperation between law enforcement agencies and other relevant agencies. The article presents a valid baseline for further research on the phenomenon, e.g. related to the projected increase in weapons saturation in the region. The paper is one means of publicising the results of research conducted by the Analytical Research Team for Illicit Markets, founded in 2012. The research was completed in 2021.